Community-based behavioural activation for depression in adolescents: feasibility study, survey and stakeholder consultations - Tindall, Lucy; Hayward, Emily; Li, Jinshuo; Kerrigan, Philip; Metcalfe, Susan; Gega, Lina (Frontiers in Child and Adolescent Psychiatry, 2025)
BackgroundBehavioural activation, a brief psychological therapy for depression across the lifespan lends itself well for delivery in community settings (e.g., non-hospital health services, schools, charities). Ahead of a randomised controlled trial, we wanted to “road-test” our recruitment and assessment processes, intervention materials and data collection tools, and understand (1): how BA can be delivered in community settings and by whom, (2) whether young people will adopt and complete it, (3) whether there are any observed changes in depression and anxiety and (4) whether usual care would be a feasible comparator.MethodsIn three settings—one community-based child and adolescent mental health service, one school, one charity—we offered up to 8 sessions of behavioural activation to 12–18-year-olds with mild-to-moderate depression. Stakeholder consultations helped us develop our research materials and processes. Self-report questionnaires assessing depression, anxiety, quality-of-life and resource use were completed by participants at baseline and 8-weeks. Professionals completed an online questionnaire about usual care for young people with depression in different settings, including types of support and staff delivering it.ResultsTwenty young people (average age 15 years, 17 females) consented; of those, 19 attended behavioural activation sessions (M = 7.4, SD: 1.5) and all 20 completed baseline and follow-up measures. For three-quarters of participants there was a “positive” change in scores (defined as a drop of ≥1 on the RCADS) from baseline to follow-up across all measures. A Resource Use Questionnaire for Adolescents collecting information about use of hospital and community-based health and social care services was developed and tested during the study. Intervention costs were modest at £207 (SD: £79) per participant for just over 5 h (M = 286 min, SD = 63 min) of contact on average with a professional.ConclusionsExcellent intervention uptake and adherence (implying robust recruitment and assessment processes), retention to follow-up and data completeness, and a positive direction of change across all outcome measures justify the need for a fully powered randomised controlled trial comparing community-based behavioural activation with usual care for adolescents with mild-to-moderate depression. Furthermore, usual care rarely included behavioural activation, which made it a suitable comparator for a future randomised controlled trial. Trial Registrationhttps://doi.org/10.1186/ISRCTN30483950, identifier (ISRCTN, ISRCTN304839502).